Characterization and evaluation of fungicides for control of Phytophthora palmivora on cocoa (Theobroma cacao) - Ong, S.N.; Leong, Sui Sien; Kwan, Yee Min (Malaysian Society of Plant Physiology, 2019)
Studies were conducted to characterize and evaluate selected fungicides against Phytophthora palmivora on cocoa (Theobroma cacao) from Sarawak, Malaysia. Based on morphological characteristics and molecular data (sequence analysis of internal transcribed spacer region and phylogenetic analysis), the causal pathogen was identified as P. palmivora. Fungicides, including copper oxychloride, metalaxyl, benzalkonium chloride, and a biofertilizer, Bacillus subtilis were evaluated for their ability to inhibit the mycelium growth of P. palmivora isolates. Benzalkonium chloride and metalaxyl exhibited 100% inhibitory effect against P. palmivorain vitro, at effective concentration (EC50) of 0.2% and 0.3 μg/mL, respectively. B. subtilis and copper oxychloride provided over 85% efficacy, with EC50 estimated at 0.35% and 1500 μg/mL, respectively. Therefore, benzalkonium chloride and B. subtilis are a good alternative for rotation with the commonly used active ingredients (metalaxyl and copper oxychloride) for P. palmivora control and management of resistance. The in vitro study has demonstrated good control of P. palmivora but in vivo study is required to account the environment factor and systemic response of the plant.